2023
DOI: 10.3390/jintelligence11090175
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Local Structural Equation Models

Alexander Robitzsch

Abstract: Local structural equation models (LSEM) are structural equation models that study model parameters as a function of a moderator. This article reviews and extends LSEM estimation methods and discusses the implementation in the R package sirt. In previous studies, LSEM was fitted as a sequence of models separately evaluated as each value of the moderator variables. In this article, a joint estimation approach is proposed that is a simultaneous estimation method across all moderator values and also allows some mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 109 publications
1
2
0
Order By: Relevance
“…It can, therefore, be concluded that the created hypothetical model confirms the fact that it is applicable in this form, as it shows a good degree of agreement with real data. This statement is confirmed also by values of other indicators: χ2 = 507.962, df = 468, p = 0.098, and it is in accordance with the theory presented in [40,43,47,60,61].…”
Section: The Model Of Cybersecuritysupporting
confidence: 88%
“…It can, therefore, be concluded that the created hypothetical model confirms the fact that it is applicable in this form, as it shows a good degree of agreement with real data. This statement is confirmed also by values of other indicators: χ2 = 507.962, df = 468, p = 0.098, and it is in accordance with the theory presented in [40,43,47,60,61].…”
Section: The Model Of Cybersecuritysupporting
confidence: 88%
“…While this method simplified the analysis, it introduced the risk of artificial dichotomization. We acknowledge the potential benefits of employing the moderated factor model or local structural equation modeling, as recommended by Molenaar et al ( 2010 ) and Robitzsch ( 2023 ), which evaluates if personality factor loadings vary across levels of cognitive ability. This approach, which models cognitive ability on a continuous scale, could complement traditional categorization methods by providing additional insights into how factor loadings vary with cognitive ability levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors consider that the selection of the measurement invariance method appears to lack a clear rationale. In theory, local structural equation modeling (LSEM) [44] and moderated nonlinear factor analysis (MNLFA) [45,46] are considered more appropriate methodologies when compared to the use of multiple-group confirmatory factor analysis.…”
Section: Discussionmentioning
confidence: 99%